Receptor mechanisms for 5-hydroxytryptamine in rabbit arteries - Black, J.L. (1981)
1 Previous investigations into the vascular actions of biogenic amines implicated in migraine have shown that the contractile effects of both 5-hydroxytryptamine (5-HT) and noradrenaline (NA) in the rabbit ear artery are mediated by a direct sympathomimetic action at α-adrenoceptors, while in the rabbit aorta, 5-HT and NA act on pharmacologically distinct receptors. The purpose of the present investigation was to determine whether the absence of 5-HT receptors in rabbit ear arteries is characteristic of distributing arteries in general, or is confined to particular regional circulations. 2 Agonist-antagonist interactions were studied in various rabbit vascular preparations (common carotid, external carotid and femoral arterial strips, and perfused ear arteries) by determining pA(2) values for pizotifen and phentolamine against 5-HT- and NA-induced contractile responses. 3 In common carotid and femoral arteries, pizotifen was a potent competitive antagonist of 5-HT, but weak against NA. The converse applied to phentolamine. In external carotid and ear arteries, pizotifen was a weak competitive antagonist of both 5-HT and NA, whereas phentolamine was a potent competitive antagonist of both. Cocaine did not influence pA(2) values against NA. 4 5-HT and NA were of similar potency in common carotid and femoral arteries, but 5-HT was much less potent than NA in external carotid and ear arteries. 5 The results indicate that rabbit common carotid and femoral arteries contain both D-type 5-HT receptors and α-adrenoceptors, as does the aorta. However, external carotid arteries, like ear arteries, do not contain specific 5-HT receptors. The action of 5-HT in the external carotid artery is mediated by α-adrenoceptors; this is a direct sympathomimetic action since it was not inhibited by cocaine or reserpine-pretreatment. 6 The absence of 5-HT receptors in the rabbit extracranial circulation may limit the usefulness of this species as a model for research relating to migraine.